IDENTIFIKASI PENGARUH FASILITAS NIAGA TERHADAP HARGA TANAH DI BANDUNG TIMUR DENGAN GEOGRAPHICALLY WEIGHTED REGRESSION (GWR) - Simarmata, Dinatasari
The price of land in an area can be influenced by several factors, one of which is the location of the land. The location of a land parcel is usually related to the proximity of the land parcel to public facilities, which in this study will focus on the proximity of the land parcel to commercial facilities. The purpose of this study is to find out which commercial facilities have the most influence on land prices in the East Bandung area. The method used is Geographically Weighted Regression (GWR). GWR is a statistical method used to model data by considering spatial aspects. Each parameter value is estimated at each point of observation location, so that each point has a different parameter value. The weighting function used for this GWR model is bi-square with a fixed bandwidth kernel type. In data processing, the independent variable is the distance from the sample point to the commercial facilities and the dependent variable is the land price. The result is parameter estimation in the form of constants and coefficients forming land prices and their error values. A land price prediction model was formed from the estimated parameters and the RMSE value was Rp. 223,124/m2. The analysis is done by identifying the regression coefficient of commercial facilities. A negative regression coefficient has an effect on increasing land prices, while a positive regression coefficient has an effect on lowering land prices. Commercial facilities that have the greatest influence on increasing land prices sequentially are bank offices, city trade and commercial centers, shop houses/offices, warehousing centers/container/cargo terminals, shops, trade centers, and other business centers. An analysis of the land price model formed and the area with high residues was also carried out.